Fermion dynamical-symmetrical model and the structure of states of the γ - nuclei - Каптагай, Г. А.; Койлык , Н.; Бактыбаев, К.; Айдарбекова , А.; Далелханкызы , А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The fermion dynamical symmetry model is a powerful method for describing the microscopic structure of collective excitations in heavy nuclei. By assuming that coherent S and D pairs are the most important building blocks in low-energy collective states the model is deeply rooted in the shell structure of nuclei. The isotopes of Pt are analyzed extensively and the concept of an effective SO(6) symmetry in the theory is examined. The fermion dynamical symmetry is an important and defining feature of many-particle systems describing different types of motion of particles in them. Mathematically, it allows you to obtain both simple analytical and numerical solutions to the quantum multiparty problem. At the same time, if we are able to split the full Hamiltonian of the fermion tasks into parts corresponding to the symmetries that are responsible for various types of motion of the nucleon system, including the parts responsible for the broken symmetries, it may be a much easier math problem that leads to a deep and consistent understanding of the nature of collective and partial movement in nucleon systems.